Chromogenic in Situ Hybridization for Human Cytomegalovirus-DNA Detection in Tissue Subsets with Prostatic Adenocarcinoma and Benign Hyperplasia - Hassan, Tayseer Anmar; AL-Saffar, Jenan M. Jawad; Mohammed Ali, Saad Hasan (Iraqi Journal of Science, 2021)
Human cytomegalovirus (HCMV) infects a wide range of human cells, resulting in both benign and malignant tumors. In the last few decades, proteins and/or nucleic acids of the virus were found to be often highly expressed in in patients with basal cell hyperplasia and prostatic neoplasia. This research aimed to unravel the rate of HCMV infections among prostatic tissue subsets from Iraqi patients with adenocarcinoma and benign hyperplasia. One hundred, formalin-fixed and paraffin embedded prostatic tissues were obtained from 40 tissue samples collected from different grades of prostate carcinoma; 40 from benign prostatic hyperplasia and 20 from apparently healthy prostatic tissues. These tissue specimens were collected from the archives of different public and private histopathological laboratories in Baghdad. Detection of HCMV-DNA was achieved by a highly sensitive version of chromogenic in situ hybridization technique. The signals of chromogenic in situ hybridization reactions for HCMV-DNA detection in prostatic adenocarcinoma tissues were found in 65% (26 out of 40) of the tissues, whereas in BPH (Benign Prostatic Hyperplasia), HCMV-DNA was detected in 57.5% (23 out of 40) of the tissues, and in the healthy control group in 25% (5 out of 20) of the tissues. The highest percentage of positive- HCMV- DNA-CISH reactions (57.5%) was found in prostatic adenocarcinomatous tissues that showed poor differentiation. Our results could show that HCMV might contribute to the development of the studied subsets of prostatic adenocarcinoma and benign prostatic hyperplasia.